Investigating Interleukin-18 Involvement And Its Modulatory Effects On Major Cytokines Release During Malaria Infection In Mice - Hasballah, Kartini (2010)
IL-18 is a potent proinflammatory cytokine that plays multiple roles in immune responses and inflammatory activities in many disease conditions, but its involvement in the underlying pathogenesis of malaria has not been fully elucidated. In this study, the role and involvement of IL-18 during malaria infection was investigated and the impact of its pathway modulation on the course of the infection and the major cytokines released during the infection was preliminary evaluated. Plasmodium berghei ANKA infection in ICR mice were used as malaria model throughout the study. The animals were inoculated intravenously with 2 x 107 parasitized red blood cells (PRBCs) obtained from a donor mouse infected with the parasite. The control animals received an equivalent volume and dilution (0.2 mL, i.v.) of normal mouse RBC. Results demonstrated that the malarial mice showed sick behavioral changes on day 4 after inoculation when the levels of parasitaemia were ≥ 60% and then continued to increase until circulating parasitaemia reached around 80%. The infected mice succumbed to hyperparasitaemia 5-6 days after infection. ICR mice also showed significant decrease in body temperature and body weight during the peak parasitaemia. IL-18 concentrations in the plasma determined by means of ELISA, showed significant elevation throughout the infection and a positive correlation with parasitaemia development.